2015
DOI: 10.1002/rhc3.12089
|View full text |Cite
|
Sign up to set email alerts
|

Flood Damage and Victims' Perceptions About Political Leadership

Abstract: To understand the extent to which material damage suffered by the flood victims correlated with views on political leadership. Using original data on 450 residents affected by the 2010 Pakistan floods collected through surveys, we carried out multiple regression analysis to understand the connections between flood damage, gender, annual income and education on the flood victims' perception of political leadership. We use open ended questions to allow for qualitative analysis along with a quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We also assigned counties (or mapping jurisdictions in the cases of New York City and the Hampton Roads region, for example) a coastal dummy variable of “1” if they fell along the Atlantic, Gulf, or Pacific coasts according to NOAA (Strategic Environmental Assessment Division, ). These data, which includes socioeconomic characteristics, NFIP participation rates, political leanings, and scientific beliefs, were chosen because they have been discussed in prior literature or public debates as influencing flood mapping (Akbar & Aldrich, ; Bakkensen & Barrage, ; Baldauf, Garlappi, & Yannelis, ; Keller et al, ; Maantay & Maroko, ; Pralle , ; Sarmiento & Miller, ). Many of our variables serve as proxies for community size, wealth, and risk expertise, which we hypothesize, based on both academic literature and news articles on the topic, will influence the interest and ability of a community to contest flood maps.…”
Section: Methodology To Evaluate County‐level Map Adoption Heterogeneitymentioning
confidence: 99%
“…We also assigned counties (or mapping jurisdictions in the cases of New York City and the Hampton Roads region, for example) a coastal dummy variable of “1” if they fell along the Atlantic, Gulf, or Pacific coasts according to NOAA (Strategic Environmental Assessment Division, ). These data, which includes socioeconomic characteristics, NFIP participation rates, political leanings, and scientific beliefs, were chosen because they have been discussed in prior literature or public debates as influencing flood mapping (Akbar & Aldrich, ; Bakkensen & Barrage, ; Baldauf, Garlappi, & Yannelis, ; Keller et al, ; Maantay & Maroko, ; Pralle , ; Sarmiento & Miller, ). Many of our variables serve as proxies for community size, wealth, and risk expertise, which we hypothesize, based on both academic literature and news articles on the topic, will influence the interest and ability of a community to contest flood maps.…”
Section: Methodology To Evaluate County‐level Map Adoption Heterogeneitymentioning
confidence: 99%
“…Research on the 2011 earthquake and tsunami in Japan identified decreasing levels of trust in government (Uslaner, ; Uslaner & Yamamura, ). Perceptions of political leadership were also negatively affected by the 2010 Pakistan floods, particularly among citizens who had suffered material damage (Akbar & Aldrich, ).…”
Section: Political Trust and Satisfaction With The Government In Relamentioning
confidence: 99%
“… Was the distribution of disaster assistance fair and just during flood recovery period? (adapted from Onstad et al., ; Akbar & Aldrich, ) …”
Section: Methodsmentioning
confidence: 99%